2008
DOI: 10.1002/j.0022-0337.2008.72.3.tb04493.x
|View full text |Cite
|
Sign up to set email alerts
|

Joining the Podcast Revolution

Abstract: In recent years, there has been a growing interest in the latest generation of web-based tools such as podcasts. Podcasts are media files that can be distributed via the Internet and played on computers and handheld devices, including iPods or other digital audio players. The essence of podcasting is the creation of audio and/or video content for an audience that wants to listen to what they want, when they want, where they want, and how they want. With students now more mobile than ever, the idea of being abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 9 publications
1
61
0
13
Order By: Relevance
“…Con base en lo mencionado, se puede decir que la implementación de esta propuesta didáctica posibilitó la generación de nuevas oportunidades para explorar en la enseñanza de la odontología, pues a través de "otros" espacios de formación, las herramientas virtuales resultaron ser muy útiles: blogs (42,43), podcasts (44), wikis (45,46), juegos (47), etc. Asimismo, generó el desarrollo de procesos didácticos desde una dinámica de interés, motivación y compromiso, con resultados provechosos para los actores implicados en el proceso: maestros-tutores y estudiantes (48).…”
Section: Resultados Y Discusiónunclassified
“…Con base en lo mencionado, se puede decir que la implementación de esta propuesta didáctica posibilitó la generación de nuevas oportunidades para explorar en la enseñanza de la odontología, pues a través de "otros" espacios de formación, las herramientas virtuales resultaron ser muy útiles: blogs (42,43), podcasts (44), wikis (45,46), juegos (47), etc. Asimismo, generó el desarrollo de procesos didácticos desde una dinámica de interés, motivación y compromiso, con resultados provechosos para los actores implicados en el proceso: maestros-tutores y estudiantes (48).…”
Section: Resultados Y Discusiónunclassified
“…Similarly, Bhatti noted that students may have difficulty with online accessibility (Bhatti et al, 2009). Previous studies have identified other drawbacks such as technical issues with hardware /software systems and production time (Bhatti et al, 2009;Jham et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the articles published over the past 5 years fall into 3 broad categories: basic how-to, student satisfaction, and student learning. Articles in the how-to category, many of which were published from 2006-2008, define key terms, describe the technologies, and outline methods of producing podcasts and distributing recordings (Cain & Fox, 2009;Corl, Johnson, Rowell, & Fishman, 2008;Elkind, 2009;Hopp, 2010;Jham, Duraes, Strassler, & Sensi, 2008;Kennedy, Gray, & Tse, 2008;Long & Edwards, 2010;McCartney, 2006;Rowell, Corl, Johnson, & Fishman, 2006;Ruiz, Mintzer, & Leipzig, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The media, early adopters of podcasting, offer radio shows via downloadable podcasts in areas such as health and science. Although podcasting appears in the academic literature as a method of presenting asynchronous on-line lecture material in higher education (Abdous, Facer & Yen, 2012;Bolliger, Supanakorn, & Boggs, 2010;Cartney, 2013;Harris, 2008;Heilesen, 2010;Hew, 2009;O'Bannon, 2011;Shantikumar, 2009), there is little that addresses the utility of open access podcasting as a tool to further disciplinary knowledge beyond a narrowly defined target audience such as students, and to cross geographical and discipline specific boundaries with the exception of some early papers on podcasting in astronomy and health Jham, Duraes, Strassler & Sensi, 2008;Price, Gay, Searle, Brissenden, 2006;Savel, Goldstein, Perencevich & Angood, 2007).…”
Section: Impact Of Social Work Podcastingmentioning
confidence: 99%